Size-controlled the gold nanoparticles on silicon suboxide film grown by vapor deposition techniques / Chan Kee Wah - Chan, Kee Wah (2012)
In this work, size-control of the gold nanoparticles (Au NPs) on silicon suboxide (SiOx) film grown by vapor deposition techniques was studied. Investigation of the effects of surrounding medium on the structural properties of Au NPs was studied first. RF magnetron co-sputtering technique was used to prepare “supported ON” and “embedded IN” structure of Au/SiOx films. As-prepared samples were annealed at different temperatures from 400 to 1000 oC to study the effect of annealing temperature on the growth of Au NPs. For both structures of Au/SiOx film, size and shape of Au NPs were observed to be temperature-dependent. Au NPs embedded IN SiOx film seemed to appear and distribute uniformly on the surface of SiOx film at 800 oC, while, Au NPs deposited on the surface of SiOx film demonstrated a uniform dispersion of elongated and island-like Au particles at 400 oC. The shape of particles changed to spherical-like as annealing temperature gradually increases from 400 to 800 oC. Growth of closely packed SiOx nanowires (NWs), which follows the solid-liquid-solid (SLS) growth mechanism, was observed at 1000 oC. Position and width of surface plasmon resonance (SPR) peak were greatly dependent on the size and shape of Au NPs. For the second part of this work, only Au/SiOx film with “supported ON” structure was studied due to its intriguing morphological properties besides simple controlled synthesis method. Homebuilt plasma-enhanced chemical vapor deposition (PECVD) technique and direct current (DC) sputter coater were introduced to prepare Au on SiOx film. Effect of N2O/SiH4 flow rate ratio on growth of Au NPs was studied with annealing temperature being kept constant at 800 oC. High concentrations of Au NPs were distributed evenly on the surface of SiOx film prepared at optimal flow rate ratio of 30. Annealing process improved the SPR peak for all as-deposited samples. FWHM of SPR peak was the dominant factor to correlate with the size of Au particle. In order to reduce unnecessary contamination that may occurred during the removal of sample from vacuum chamber to sputter coater, a one-step process was introduced - Hot Wire Assisted PECVD technique. Evaporation of Au controlled by a shutter was carried out in a vacuum chamber immediately after the deposition of SiOx film at optimal flow rate ratio of 30. Role of SiOx film as a barrier for preventing agglomeration of Au NPs was studied. It was confirmed that the weak Au-SiOx chemical interaction allows the precise study of Au NPs alone by eliminating other unwanted factors. Lastly, the effect of substrate heating on the growth of Au NPs was investigated to determine the possibility of preparing a uniform and smaller size of Au NPs without using the post thermal-annealing technique. It was found that Au NPs with uniform size around 6.45 nm can be obtained as substrate temperature is set at 300 oC. No formation of NPs can be observed below 300 oC. Further thermal annealing process at lower temperature of 200 oC was shown to improve the distribution of Au NPs. FWHM of SPR peak became narrowed as inter-particle distance of Au NPs increased due to a broader size distribution.